MRI findings of intraosseous lipoma: case report - Ozdemir, H; Bozgeyik, Z; Kocakoc, E; Kalender, O (Elsevier Science Inc, 2004)
Intraosseous lipoma is one of the rarest benign bone tumors and usually presents in the fourth to fifth decades. Except for minor symptoms, they are usually asymtomatic. Metaphysis of long bones, especially proximal parts of femur and fibula, are involved in most cases. We present intraosseous lipoma to discuss the benefits of MRI and contrast-enhanced MRI findings for differential diagnosis. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: intraosseous lipoma; femur; tumor; magnetic resonance imaging